Epoxy-based thermal interface materials
The two-component epoxy-based TIM composition, with a high content of aluminum trihydroxide (ATH) and a specific epoxy resin and curing agent formulation, addresses the challenges of thermal management in high-density battery-powered vehicles by providing improved thermal conductivity and stability.
Patent Information
- Application Number
- JP2022530648
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-26
- Filing Date
- 2020-10-06
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2040-10-06
AI Technical Summary
Current thermal interface materials (TIMs) for high-density battery-powered vehicles face challenges due to the high cost and abrasiveness of thermally conductive fillers like boron nitride or aluminum powder, and the need for high amounts of aluminum trihydroxide (ATH) to achieve sufficient thermal conductivity while maintaining thermal stability.
A two-component epoxy-based thermal interface material (TIM) composition is developed, which includes epoxy resin composition A and curing composition B. The composition features a liquid epoxy resin without aromatic groups, a curing agent, and a volume ratio between the two components ranging from 1:10 to 10:1. The TIM composition incorporates aluminum trihydroxide (ATH) in amounts of 80-95% by weight, providing improved thermal conductivity and stability.
The proposed TIM composition achieves enhanced thermal conductivity and stability, effectively addressing the challenges of cost, abrasiveness, and thermal management in high-density battery-powered vehicles, while maintaining mechanical properties even after heat aging.
Smart Images

Figure 0007665617000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to thermal interface materials and their use in battery powered vehicles. [Background technology]
[0002] Compared to traditional modes of transportation, battery-powered vehicles have significant advantages such as light weight and reduced CO2 emissions. However, many technical challenges still need to be overcome to ensure optimal use of the technology. For example, one of the current efforts in the industry is to increase the driving range of battery-powered vehicles by developing higher density batteries. This leads to the need to develop better thermal management systems for high density batteries.
[0003] In battery-powered vehicles, the battery cells or modules are thermally connected to the cooling unit by thermal interface materials (TIMs). Such TIMs are typically formed from polymer-based materials filled with thermally conductive fillers. To achieve thermal conductivities of 2 W / m·K or more, fillers with thermal conductivities of 100 W / m·K or more, such as boron nitride or aluminum powder, can be used. However, such fillers are expensive and abrasive. A cheaper, non-abrasive alternative is aluminum trihydroxide (ATH). Due to its low thermal conductivity of about 10 W / m·K, high loadings of ATH (i.e., 80 wt.% or more) are required. Furthermore, it is highly desirable that the TIM is also thermally stable. Summary of the Invention [Means for solving the problem]
[0004] Disclosed herein is a thermal interface material (TIM) composition prepared by combining an epoxy resin composition A and a curing composition B, where (i) the epoxy resin composition A comprises at least one liquid epoxy resin that does not contain aromatic groups, (ii) the curing composition B comprises at least one curing agent, (iii) the volume ratio between the epoxy resin composition A and the curing composition B ranges between about 1:10 to 10:1; and (iv) the epoxy resin composition A, the curing composition B, or both further comprise aluminum trihydroxide (ATH), such that the ATH is present in the TIM composition in an amount of about 80 to 95 wt%, based on the total weight of the TIM composition.
[0005] In a further embodiment of the TIM composition, the volume ratio between the epoxy resin composition A and the curing composition B is about 1:2 to 2:1.
[0006] In still further embodiments of the TIM composition, the at least one liquid epoxy resin is selected from epoxide ethers having an epoxy equivalent weight (EEW) of about 200 to 500 g / eq.
[0007] In still a further embodiment of the TIM composition, the at least one liquid epoxy resin is selected from epoxide ethers having a weight average molecular weight of 400-800.
[0008] In still further embodiments of the TIM composition, the at least one curing agent is selected from the group consisting of polymeric amines, polymeric amides, low molecular weight amines, and combinations of two or more thereof.
[0009] In yet a further embodiment of the TIM composition, about 80-95 wt. % of ATH is included in epoxy resin composition A, based on the total weight of epoxy resin composition A, and about 80-95 wt. % of ATH is included in cured composition B, based on the total weight of cured composition B.
[0010] In still further embodiments of the TIM composition, the epoxy resin composition A, the curing composition B, or both further comprise at least one cure accelerator.
[0011] In still further embodiments of the TIM composition, the at least one cure accelerator is a compound selected from the group consisting of tertiary amines, organotin catalysts, ammonium salts, phenolic catalysts, urea catalysts, and mixtures thereof.
[0012] In yet a further embodiment of the TIM composition, the at least one cure accelerator is included in an amount of about 0.01 to 5 weight percent, based on the total weight of the TIM composition.
[0013] In still further embodiments of the TIM composition, the ATH has an average particle size in the range of about 5 to 100 μm.
[0014] In still further embodiments of the TIM composition, the ATH has a multimodal particle size distribution.
[0015] Further disclosed herein are articles that include the TIM compositions described below.
[0016] In a further embodiment of this article, it further comprises a battery module formed from one or more battery cells and a cooling unit, the battery module being connected to the cooling unit via the TIM composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] As is known in the art, in two-component epoxy adhesives, curing can be carried out at ambient conditions, such that the adhesive comprises at least two different compositions (an epoxy resin composition and a curing composition) that are kept separate until use. The epoxy resin composition typically contains one or more epoxy resins and other ingredients and additives for various reasons. The curing composition, on the other hand, typically contains one or more hardening or curing agents. The curing composition also typically contains other additives for various reasons. The curing composition typically does not contain an epoxy resin. In addition, it is preferred that at least one curing accelerator or catalyst (allowing for curing at non-high temperatures) is included in the epoxy resin composition or the curing composition or both.
[0018] Disclosed herein is a two-component epoxy-based thermal interface material (TIM) composition prepared by combining an epoxy resin composition A and a curing composition B. The epoxy resin composition A comprises at least one liquid epoxy resin that does not contain aromatic groups, and the curing composition B comprises at least one curing agent. In accordance with the present disclosure, the epoxy resin A and the curing composition B are included in the TIM composition in a volume ratio ranging from about 1:10 to 10:1. Additionally, the epoxy resin composition A, the curing composition B, or both, further comprise aluminum trihydroxide (ATH), such that about 80 to 95 wt % of ATH is included in the final two-component epoxy-based TIM composition, based on the total weight of the TIM composition.
[0019] The liquid epoxy resins used herein can be any organic compound having at least one oxirane ring that is polymerizable by a ring-opening reaction. Such materials, also known as epoxides, include both monomeric and polymeric epoxides. The liquid epoxy resins used herein do not have aromatic rings and can be, for example, aliphatic, cycloaliphatic, heterocyclic, or cycloaliphatic, or even combinations thereof. The liquid epoxy resins used herein are selected to have a low Tg (e.g., below room temperature) to provide good tack and adhesion. The polymeric epoxides used herein include, but are not limited to, linear polymers with terminal epoxy groups (e.g., diglycidyl ethers of polyoxyalkylene glycols), polymers with oxirane backbone units (e.g., polybutadiene polyepoxides), and polymers with epoxy side groups (e.g., glycidyl methacrylate polymers or copolymers). The weight average molecular weight of the epoxy resin can be about 90 to 2000, about 200 to 2000, about 300 to 1600, about 340 to 1000, about 400 to 800, or about 600 to 700. The epoxy resin can have an epoxy equivalent weight (EEW) of about 100 to 1000 g / eq, about 150 to 800 g / eq, about 200 to 500 g / eq, or about 300 to 400 g / eq.
[0020] Exemplary aliphatic epoxides include, but are not limited to, polyglycidyl ethers of aliphatic polyhydric alcohols or their arylene oxide adducts; polyglycidyl esters of aliphatic long chain polybasic acids; homopolymers synthesized by the vinyl polymerization of glycidyl acrylate or glycidyl methacrylate; and copolymers synthesized by the vinyl polymerization of glycidyl acrylate or glycidyl methacrylate with other vinyl monomers. Further specific examples include, but are not limited to, glycidyl ethers of polyhydric alcohols such as 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol tetraglycidyl ether, dipentaerythritol hexaglycidyl ether, polyethylene glycol diglycidyl ether, and polypropylene glycol diglycidyl ether; polyether polyol polyglycidyl ethers obtained by the addition of one or more alkylene oxides to aliphatic polyhydric alcohols such as propylene glycol, trimethylolpropane, and glycerol; and diglycidyl esters of aliphatic long-chain dibasic acids. Also included may be monoglycidyl ethers of higher aliphatic alcohols, monoglycidyl ethers of phenol, cresol, butylphenol or polyether alcohols thereof obtained by addition of alkylene oxides, glycidyl esters of higher fatty acids, epoxidized soybean oil, octyl epoxy stearate, butyl epoxy stearate, and epoxidized polybutadiene.
[0021] Exemplary cycloaliphatic epoxy compounds include polyglycidyl ethers of polyhydric alcohols having at least one cycloaliphatic ring, and cyclohexene oxide- or cyclopentene oxide-containing compounds obtained by epoxidizing a cyclohexene ring- or cyclopentene ring-containing compound with an oxidizing agent.
[0022] The liquid epoxy resins used herein may be selected from commercially available products, such as DER™ 732, DER™ 732p, or DER™ 736 epoxy resins available from Dow Chemical Company; and glycidyl ethers of polyether polyols, such as Araldite™ DY-C from Huntsman.
[0023] The curing composition B includes at least one curing agent or hardener capable of crosslinking with the epoxy group of the epoxy resin. Any curing agent or hardener, such as those suitable for two-component epoxies, can be used. Exemplary curing agents include, but are not limited to, polymeric amines, polymeric amides, low molecular weight amines, and combinations of two or more thereof.
[0024] Suitable polymeric amines can be any polyamines having at least two reactive -NH groups, i.e., they can have at least one primary amine (-NH2) group or at least two secondary amine (-NH) groups, or a combination thereof. Exemplary polyamines include polyetherdiamines, polyethertriamines, and mixtures thereof. The polyetheramines used herein can be linear or branched, and they can have any suitable molecular weight. In one embodiment, the polyetheramines can have a molecular weight ranging from about 200 to 6000, or greater than 1000, or greater than 3000.
[0025] Suitable commercially available polyetheramines include those sold by Huntsman under the Jeffamine trade name. Suitable polyetherdiamines include the D, ED and DR series of Jeffamine. These include Jeffamine D-230, D-400, D-2000, D-4000, HK-511, ED-600, ED-900, ED-2003, EDR-148 and EDR-176.
[0026] Suitable polyether triamines include the Jeffamine T series, which include Jeffamine T-403, T-3000 and T-5000.
[0027] Suitable polyamides include the reaction products of dimerized fatty acids and polyamines. Examples of such polyamides include those available from Cognis under the trade names Versamid® 115, Versamid® 125 and Versamid®. Low molecular weight (non-polymeric) amines may also be included in the curing composition B as curing agents, which function as crosslinkers and / or chain extenders and include primary and / or secondary amines.
[0028] The low molecular weight amines can have a molecular weight of at least about 48 g / mol or at least about 60 g / mol, and up to about 300 g / mol, about 250 g / mol, or 200 g / mol. Exemplary low molecular weight amines include, but are not limited to, triethylenetetramine (TETA), diethylenetriamine (DETA), isophoronediamine (IPDA), and ethylenediamine.
[0029] The ATH used herein may be a unimodal ATH powder or an ATH powder having a multimodal particle size distribution (e.g., bimodal, trimodal, etc.). The average particle size of the ATH powder may range from about 5 to 100 μm. Also, when a multimodal ATH powder is used, the average particle size of the smallest particles may be less than about 10 μm, while the average particle size of the largest particles may be greater than about 50 μm. Additionally, the ATH powder used herein may be surface treated with silanes, titanates, carboxylates, and the like.
[0030] In accordance with the present disclosure, ATH powder may be included in epoxy resin composition A, curing composition B, or both, and the epoxy resin composition A and the curing composition are combined in a volume ratio ranging from about 1:10 to 10:1, or about 1:4 to 4:1, or about 1:2 to 2:1, or about 1:1 to form a two-component epoxy-based TIM composition as disclosed herein, and the ATH powder is included in epoxy resin composition A, curing composition B, or both, such that the final content of ATH in the TIM composition is in the range of about 80 to 95 wt %, or about 80 to 92 wt %, based on the total weight of the composition.
[0031] In one embodiment, epoxy resin composition A and curing composition B each comprise about 80-95 wt %, or about 80-92 wt %, of ATH, and epoxy resin composition A and curing composition B are combined in a volume ratio of about 1:1 to form a two-component epoxy-based TIM composition.
[0032] Additionally, up to about 10% by weight, or about 1-10% by weight, or about 2-7% by weight, or about 2-5% by weight of precipitated calcium carbonate can be added to epoxy resin composition A, curing composition B, or both. Without being bound to any particular theory, it is believed that the optional addition of precipitated calcium carbonate can improve anti-settling of the ATH.
[0033] Additionally, one or more curing accelerators (catalysts) may be included in the epoxy resin composition A, the curing composition B, or both to speed up the curing of the TIM composition. The curing accelerator preferably acts by catalyzing the reaction between a low molecular weight amine and a polyamine on the one hand, and with the epoxy resin on the other hand. Curing accelerators as used herein may include, but are not limited to, tertiary amines, organotin catalysts, ammonium salts, phenolic catalysts, urea catalysts, and mixtures thereof. Typical tertiary amines include, for example, tris-2,4,6-dimethylaminomethylphenol (available from Evonik under the tradename Ancamine K54) and phenol salts of diazabicycloundecene (DBU) (available from Evonik under the tradename Polycat SA1 / 10), triethylenediamine (DABCO). Exemplary organotin catalysts include, for example, dioctyltin dineodecanoate (available from Galata Chemicals under the tradename FomrezUL38). Exemplary ammonium salts include, for example, tetrabutylammonium bromide. Exemplary urea-based catalysts include, for example, the reaction product of isophorone diisocyanate with dimethylamine (available from Evonik under the trade name Omicure™ U35) and the reaction product of methylene diphenyl diisocyanate with dimethylamine.
[0034] The curing agent and optional curing accelerator may be used in the appropriate ratio and amount to reduce the required curing temperature and allow the combined parts of the two-component TIM composition to cure at the appropriate temperature. The curing temperature is preferably less than about 100°C, more preferably less than 90°C, or less than 60°C, or less than 50°C, or less than 40°C. The TIM composition is preferably cured at ambient temperature, e.g., at or between 20°C or 25°C. There is no particular preferred minimum curing temperature. In general, however, the curing temperature is generally greater than 0°C, greater than 10°C, or greater than 15°C. Curing may preferably be carried out in the range of, e.g., 10°C to 40°C, more preferably, 15°C to 35°C. For example, the TIM composition of the present invention may be heated to further reduce the curing time or to obtain a more complete cure.
[0035] In accordance with the present disclosure, the cure accelerator may be included in the TIM composition in an amount of about 0.01 to 5 wt %, or about 0.05 to 2.5 wt %, or about 0.1 to 2 wt %, based on the total weight of the TIM composition. In addition, epoxy resin composition A may optionally further comprise other suitable additives, such as plasticizers, stabilizers, adhesion promoters, fillers, colorants, etc. Such optional additives may be present in an amount of up to about 10 wt %, or up to about 8 wt %, or up to about 5 wt %, based on the total weight of epoxy resin composition A.
[0036] In accordance with the present disclosure, a two-component epoxy-based TIM is prepared by combining an epoxy resin composition A and a curing composition B, followed by mixing (e.g., using a static mixer) and curing (preferably at ambient temperature).
[0037] Further disclosed herein is a battery pack system in which a cooling unit or plate is coupled to a battery module (formed from one or more battery cells) via the epoxy-based thermal interface paste material described above, so that heat can be conducted therebetween. In one embodiment, the battery pack system is for use in a battery-powered automobile. The present invention includes the following aspects. Section 1. A thermal interface material (TIM) composition prepared by combining an epoxy resin composition A and a curing composition B, (i) said epoxy resin composition A comprises at least one liquid epoxy resin that does not contain aromatic groups; (ii) said curing composition B comprises at least one curing agent; (iii) the volume ratio between the epoxy resin composition A and the curing composition B is in the range of about 1:10 to 10:1; and (iv) The thermal interface material (TIM) composition, wherein the epoxy resin composition A, the cured composition B, or both further comprise aluminum trihydroxide (ATH), such that the ATH is present in the TIM composition in an amount of about 80-95 wt%, based on the total weight of the TIM composition. Section 2. Item 2. The TIM composition according to item 1, wherein the volume ratio between the epoxy resin composition A and the curing composition B is about 1:2 to 2:1. Section 3. Item 3. The TIM composition according to item 1 or 2, wherein the at least one liquid epoxy resin is selected from epoxide ethers having an epoxy equivalent weight (EEW) of about 200 to 500 g / eq. Section 4. Item 4. The TIM composition according to any one of items 1, 2, or 3, wherein the at least one liquid epoxy resin is selected from epoxide ethers having a weight average molecular weight of 400 to 800. Section 5. Item 5. The TIM composition according to any one of items 1 to 4, wherein the at least one curing agent is selected from the group consisting of polymeric amines, polymeric amides, low molecular weight amines, and combinations of two or more thereof. Section 6. Item 6. The TIM composition according to any one of items 1 to 5, wherein about 80 to 95 wt % of ATH is contained in the epoxy resin composition A based on the total weight of the epoxy resin composition A, and about 80 to 95 wt % of ATH is contained in the cured composition B based on the total weight of the cured composition B. Section 7. Item 7. The TIM composition according to any one of items 1 to 6, wherein the epoxy resin composition A, the curing composition B, or both further comprise at least one curing accelerator. Section 8. Item 8. The TIM composition of item 7, wherein the at least one cure accelerator is a compound selected from the group consisting of tertiary amines, organotin catalysts, ammonium salts, phenolic catalysts, urea catalysts, and mixtures thereof. Section 9. Item 9. The TIM composition according to item 7 or 8, wherein the at least one curing accelerator is contained in an amount of about 0.01 to 5 wt % based on the total weight of the TIM composition. Section 10. Item 10. The TIM composition according to any one of items 1 to 9, wherein the ATH has an average particle size in the range of about 5 to 100 μm. Section 11. 11. The TIM composition according to any one of items 1 to 10, wherein the ATH has a multimodal particle size distribution. Section 12. Item 12. An article comprising the TIM composition according to any one of items 1 to 11. Section 13. Item 13. The article of item 12, further comprising a battery module formed of one or more battery cells and a cooling unit, the battery module being connected to the cooling unit via the TIM composition. EXAMPLES
[0038] material EP-1 - an epoxy resin which is the reaction product of epichlorohydrin and polypropylene glycol and has a weight average MW of about 650 and an EEW of about 310-330 g / eq; EP-2 - an epoxy resin which is the reaction product of epichlorohydrin and bisphenol A and has a weight average MW of about 350 and an EEW of about 176-185 g / eq; · Aromatic polyisocyanate prepolymers based on toluene diisocyanate (TDI) obtained from PU-Pre-Covestro; Plasticizers - 1,2-Benzene carboxylic acid di-C8-C obtained from SASOL 10 Alkyl esters; · ATH-aluminum trihydroxide with bimodal distribution; ·CaCO3 - precipitated calcium carbonate obtained from Cary Company; · Catalyst – Dioctyltin dineodecanoate obtained from Momentive; · Colorant- green chromophore in epoxy resin. Polyamine-1 - a polyoxypropylenediamine having an average molecular weight of about 2000 available from Huntsman under the trade name Jeffamine™ D-2000; Polyamine-2 - a polyetheramine (triamine) having an average molecular weight of about 3000, available from Huntsman under the trade name Jeffamine™ T-3000; Accelerator - Tris-2,4,6-dimethylaminomethylphenol obtained from Evonik; ·Fatty acid-unsaturated C 16 ~C 18 Methyl esters of fatty acids; · Silane-Hexadecyltrimethoxysilane;
[0039] Test Method Press-in force: The press-in force of the test material was measured by compressing it with a 40 mm aluminum cylinder from a thickness of 5 mm to 0.3 mm at 1 mm / s. The force-deflection curve was monitored and the force at 0.5 mm was recorded.
[0040] Thermal Conductivity (TC): The thermal conductivity of the test materials was measured according to ASTM 5470.
[0041] Vertical cycle bleeding test: Sandwich structures (steel / TIM / glass) were made consisting of a test sample (two-component TIM) sandwiched between a layer of electrocoated steel sheet and a layer of glass sheet by using 18 g of TIM between the steel sheet and the glass sheet, and compressed (using a spacer) to a thickness of 3 mm. After 48 hours, the sandwich structures were then exposed to a climatic cycle test for 4 weeks, where each cycle took 12 hours to complete and consisted of 4 hours at -40°C (uncontrolled humidity), 4 hours to adjust the temperature to 80°C, and 4 hours at 80°C, 80% relative humidity. The sandwich panels were then visually inspected after the test, and samples without crack formation, phase separation, and slippage were rated as "good", otherwise rated as "bad".
[0042] Thermal stability: Each sample of the bicomponent TIM was pressed into a 2 mm thick plaque and then cured at room temperature for 7 days. The cured plaques were placed at 110°C for 7 days and then visually inspected for color change and mechanical properties (such as brittleness). The elastic modulus and tensile strength of the samples were then measured according to ISO 527-2.
[0043] Pull-out pressure: Two (2) aluminum cylinders (25 mm diameter) were bonded with a 0.5 mm thick two-component TIM and cured for 7 days at 23°C and 50% relative humidity. The two cylinders were then pulled apart on a Zwick tensometer at a rate of 0.5 mm / s and the force deflection curve was measured. The maximum force (at break) was recorded and divided by the area to obtain the pull-out pressure in MPa.
[0044] Comparative Examples CE1 to CE2 and Example E1 In each of Comparative Examples CE1-CE1 and Example E1, Composition A and Composition B were prepared separately by mixing the ingredients listed in Table 1. The press-in force was measured and recorded for each of Compositions A and B (uncured). Compositions A and B were then mixed together using a side-by-side cartridge and an air-operated application gun, and then mixed using a static mixer. The press-in force, thermal conductivity, vertical cycle bleeding test, thermal stability, and pull-out pressure of the TIM materials were measured and the results are listed in Table 1.
[0045] Compared with polyurethane-based TIM, epoxy-based TIM as demonstrated herein has a greatly improved thermal stability. Furthermore, the data demonstrates that when an epoxy resin with an aromatic ring is used, the press-in force of epoxy resin composition A becomes too high to be useful. In particular, when forming the two-component TIM in CE2, composition A was applied with a manual application gun using a static mixer, but the application took a very long time to complete. Furthermore, the TIM in CE2 has a much higher elastic modulus (294 MPa) and withdrawal pressure (0.2 MPa), which are not useful for applying thermal interface materials. Furthermore, the mechanical properties of the TIM in E1 were maintained even after heat aging at 110°C for 7 days.
[0046] [Table 1]
Claims
1. A thermal interface material (TIM) composition prepared by combining an epoxy resin composition A and a curing composition B, (i) the epoxy resin composition A is at least one liquid epoxy resin selected from epoxide ethers having an epoxy equivalent weight (EEW) of 310 to 330 g / eq and a weight average molecular weight of 400 to 800, which does not contain aromatic groups; (ii) said curing composition B comprises at least one curing agent; (iii) the volume ratio between the epoxy resin composition A and the curing composition B ranges between 1:2 and 2:1; and (iv) The thermal interface material (TIM) composition, wherein the epoxy resin composition A, the cured composition B, or both further comprise aluminum trihydroxide (ATH), such that the ATH is present in the TIM composition in an amount of 80 to 95 wt %, based on the total weight of the TIM composition.
2. 10. The TIM composition of claim 1, wherein the at least one curing agent is selected from the group consisting of polymeric amines, polymeric amides, low molecular weight amines having a molecular weight of 48 to 300, and combinations of two or more thereof.
3. The TIM composition described in claim 1 or 2, wherein 80 to 95 weight % of ATH is contained in the epoxy resin composition A based on the total weight of the epoxy resin composition A, and 80 to 95 weight % of ATH is contained in the cured composition B based on the total weight of the cured composition B.
4. The TIM composition of any one of claims 1 to 3, wherein the epoxy resin composition A, the curing composition B, or both further comprise at least one curing accelerator.
5. 5. The TIM composition of claim 4, wherein the at least one cure accelerator is a compound selected from the group consisting of tertiary amines, organotin catalysts, ammonium salts, phenolic catalysts, urea catalysts, and mixtures thereof.
6. The TIM composition of claim 4 or 5, wherein the at least one cure accelerator is included in an amount of 0.01 to 5 wt %, based on the total weight of the TIM composition.
7. The TIM composition of any one of claims 1 to 6, wherein the ATH has an average particle size in the range of 5 to 100 μm.
8. The TIM composition of any one of claims 1 to 7, wherein the ATH has a multimodal particle size distribution.
9. An article comprising a TIM composition according to any one of claims 1 to 8.
10. 10. The article of claim 9, further comprising a battery module formed from one or more battery cells and a cooling unit, the battery module being connected to the cooling unit via the TIM composition.
Citation Information
Patent Citations
Two-component potting composition
JP2015021118A
Composition including a polythiol, a polyepoxide, an amine catalyst, and a conductive filler and methods relating to the composition
US20210403700A1
Thermally conductive resin composition, cured product thereof, and thermally conductive sheet and method for manufacturing same
WO2018154832A1